PEMANFAATAN IKAN Chanos chanos SEBAGAI PRODUK ENTREPRENEUR DI KECAMATAN BALONGAN - Lissa, Lissa; Hamidah, Idah; Nurazizah, Eva; Lutfiat, Nina; Antika, Rindi (UNIVERSITAS PGRI MADIUN, 2022)
Abstract. The purpose of this service is to optimize the potential of natural and human resources so that they have better economic value. In this case, Milkfish in Balongan District. Balongan District is located in Indramayu Regency, West Java. Balongan is a coastal area with the majority of its people's livelihood as fishermen, Milkfish is an abundant commodity, especially when the harvest comes, this makes milkfish have a low selling price. The implementation method uses PRA (Participatory Rural Appraisal) with the object of activity being the community while lecturers and students as facilitators, while the stages of the activities are 1) potential analysis, 2) preparation of activity plans, 3) inauguration, 4) training, and 5) evaluation and follow-up. The entrepreneur product as a result of this service activity is shredded milkfish (BonDeng), the product is made on a small scale then tested organolepticn, After that, together with the Balongan fishing community, the product is made on a medium scale and marketed. The resulting product is still one type and more varied products are needed. Evaluation of Shredded Milkfish (BonDeng) still needs to improve the quality of oil drying and packaging so that a better product will be obtained. Abstrak. Tujuan dari pengabdian ini adalah untuk mengoptimalkan potensi Sumber Daya Alam dan manusia sehingga memiliki nilai ekonomi yang lebih baik. Dalam hal ini Ikan Bandeng di Kecamatan Balongan. Kecamatan Balongan terletak di Kabupaten Indramayu, Jawa barat. Balongan merupakan daerah pesisir dengan mayoritas pencaharian masyarakatnya sebagai nelayan, ikan bandeng merupakan komoditi yang melimpah apalagi saat panen datang, hal ini menjadikan ikan bandeng memiliki harga jual yang rendah. Metode pelaksanaan menggunakan PRA (Participatori Rural Appraisal) dengan pelaku utama atau objek kegiatan adalah masyarakat sedangkan dosen dan mahasiswa sebagai fasilitator, adapun tahapan kegiatannya yaitu 1) analisa potensi, 2) penyusunan perencanaan kegiatan, 3) penyukuhan, 4) pelatihan, dan 5) evaluasi dan tindak lanjut. Produk enterpreneur hasil kegiatan pengabdian ini adalah abon ikan bandeng (BonDeng), produk dibuat dalam skala kecil kemudian diuji organoleptik, setelah itu bersama dengan komunitas nelayan Balongan produk dibuat dalam skala menengah dan dipasarkan. Produk yang dihasilkan masih satu jenis dan dibutuhkan produk yang lebih variatif. Evaluasi abon Bandeng (BonDeng) masih perlu ditingkatkan kualitas pengeringan minyak dan pengemasan sehingga akan didapatkan produk yang lebih baik.